ANALISIS EFEKTIVITAS SISTEM PENGENDALIAN INTERNAL ATAS PERSEDIAAN BARANG DAGANG DENGAN PROGRAM ASSCEND ENTERPRICE RESOURCE PLANNING (AERP) PADA PT SINAR PRIMA LESTARI - Pangaribuan, Corry Lucky; Samosir, Hendrik E.S; Lumban Gaol , Vebry M (Jurnal Akuntansi Kompetif, 2025)
This study aims to analyze the effectiveness of the internal control system on merchandise inventory through the implementation of the Asscend Enterprise Resource Planning (AERP) program at PT Sinar Prima Lestari. A reliable internal control system is essential to ensure the accuracy of inventory data and to minimize the risks of loss, fraud, and recording errors. This research employ ys a descriptive qualitative method, with data collected through observation, direct interviews with relevant personnel, and system documentation. The results indicate that the implementation of the AERP system has supported the effectiveness of the company’s internal control by enabling automated recording, transaction authorization features, and real-time interdepartmental integration. The program has improved efficiency, transparency, and reduced manual errors in inventory management. However, some weaknesses were identified in practice, such as delayed data input and dependence on manual supervision. Overall, the internal control system based on AERP at PT Sinar Prima Lestari has been reasonably effective but still requires improvement in terms of user discipline and regular training.